(T~,S)-CUBİC HYPER KU-İDEALS - Samy Mohammed Mostafa (Journal of New Theory)
– It is known that, the concept of hyper KU–algebras is a generalization of KU–algebras. In this paper, the concepts (T,S)– cubic theory of the (s-weak – strong) hyper KU-ideals in hyper KU–algebras are applied and the relations among them are obtained. ~